Efetividade de infiltrações de hialuronato de sódio no tratamento de desordens temporomandibulares articulares - Roberta Maria Drumond Furtado B. Fonseca (2016)
Viscosupplementation is a minimally invasive technique that replaces synovial fluid by intra-articular injection of hyaluronic acid (HA). Although it has been effective in some joints, there is not conclusive evidence regarding temporomandibular disorders. This case series describes efficacy of a viscosupplementation protocol in intra-articular temporomandibular disorders. Ten patients with a diagnosis of disc displacement and/or osteoarthritis by Research Diagnostic Criteria for Temporomandibular Disorders were submitted to a cycle of four monthly injections of low or medium molecular weight hyaluronic acid in superior joint space. Pain, mandibular function, image analysis by computerized tomography and magnetic resonance imaging, and measurement of inflammatory mediators in serum were assessed at baseline and follow-ups (1 and 6 months). Pain intensity, jaw range of motion, mandibular function, and quality of life improved at follow-up evaluations. Osteoarthritic changes decreased and 25% of patients improved mandibular head excursion after treatment. Resolution of effusion and improvement in disc morphology were observed for most patients. Serum levels of IL-1, IL-6, IL-8, IL-10, IL-12p70, and TNF were not detected. Viscosupplementation protocol described here reduced pain and symptoms associated with internal derangement of temporomandibular joint and improved quality of life of patients.